2009
DOI: 10.1002/jcb.22380
|View full text |Cite
|
Sign up to set email alerts
|

RAD 001 (everolimus) prevents mTOR and Akt late re‐activation in response to imatinib in chronic myeloid leukemia

Abstract: The mammalian target of rapamycin (mTOR) is one target of BCR-ABL fusion gene of chronic myeloid leukemia (CML). Moreover, it drives a compensatory route to Imatinib mesylate (IM) possibly involved in the progression of leukemic progenitors towards a drug-resistant phenotype. Accordingly, mTOR inhibitors are proposed for combined therapeutic strategies in CML. The major caveat in the use of mTOR inhibitors for cancer therapy comes from the induction of an mTOR-phosphatidylinositol 3 kinase (PI3k) feedback loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…The ability of rapamycin to promote Treg cell generation was therefore attributed to its ability to inhibit mTORC1. However, more recent studies confirmed that mTOR inhibitors as rapamycin or everolimus do inhibit mTORC2 as well, thereby causing a reduction of Akt activity in vitro and in vivo [85-88]. This fact appears to be in line with recent studies on the role of Foxo factors in regulating Foxp3 expression.…”
Section: Enhancement Of Extrathymic Treg Generationsupporting
confidence: 65%
“…The ability of rapamycin to promote Treg cell generation was therefore attributed to its ability to inhibit mTORC1. However, more recent studies confirmed that mTOR inhibitors as rapamycin or everolimus do inhibit mTORC2 as well, thereby causing a reduction of Akt activity in vitro and in vivo [85-88]. This fact appears to be in line with recent studies on the role of Foxo factors in regulating Foxp3 expression.…”
Section: Enhancement Of Extrathymic Treg Generationsupporting
confidence: 65%
“…When PP242 was combined with higher doses of dasatinib, the decrease in leukemic burden was significantly higher than with dasatinib monotherapy [17]. The combination of everolimus and imatinib enhanced the cytotoxicity induced by imatinib alone in Bcr-Abl-expressing cells via persistent inhibition of cell proliferation and apoptosis [32,33]. Greater nuclear translocation of the normal p145 c-Abl protein occurred in response to the combined presence of everolimus and imatinib, leading to apoptosis [33].…”
Section: In Vitro Data With Mtor Inhibitors In Leukemiamentioning
confidence: 99%
“…Everolimus also may have a role in the blockade of imatinib resistance in leukemic cells. One mechanism of imatinib resistance involves activation of the PI3K/Akt/mTOR pathway; however, treatment with everolimus antagonized the late reactivation of mTOR triggered by imatinib treatment in Bcr-Abl-expressing cells [32]. The T315I mutation in the Abl kinase domain coding region alters the imatinib binding site on tyrosine kinase and confers resistance to imatinib.…”
Section: In Vitro Data With Mtor Inhibitors In Leukemiamentioning
confidence: 99%
“…Currently, it is under phase I/II clinical trials (NCT00093639, www.clinicaltrials.gov) in combination with IM to treat CP CML patients who are not in complete cytogenetic remission after previous treatment with IM. Everolimus inhibits mTOR and revokes its late re-activation in response to IM [173] and enhances the effects of IM in CML by raising the nuclear expression of c-ABL proteins [174]. Ridaforolimus, previously called Deforolimus, is another mTOR inhibitor undergoing clinical trials for the treatment of aggressive, relapsed/refractory lymphoma [175] (NCT00086125, www.clinical trials.gov) and metastatic bone sarcomas [176].…”
Section: Ras/pi3k/pten/akt/mtor Pathwaymentioning
confidence: 99%